2021
DOI: 10.1016/j.eclinm.2021.100950
|View full text |Cite
|
Sign up to set email alerts
|

Structural racism and risk of SARS-CoV-2 in pregnancy

Abstract: Background: Structural racism leads to adverse health outcomes, as highlighted by inequities in COVID-19 infections. We characterized Black/White disparities among pregnant women with SARS-CoV-2 in Cuyahoga County which has some of the most extreme health disparities in the U.S., such as a rate of Black infant mortality that is three times that of White counterparts. Methods: This was a retrospective cohort study using data collected as part of public health surveillance between March 16, 2020 until October 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Moreover, the fear, distrust ( George et al., 2014 ), and historical misconduct associated with the Tuskegee study ( Shavers et al., 2000 ) may be related to the low percentage of Black or African American participants (8.9%). On a more practical level, during the pandemic, women of color were more likely to be classified as essential workers ( Pope et al., 2021 ; Rogers et al., 2020 ) and faced unemployment if they did not continue to work ( Pew Research Center, 2020a ), which may have left women without the time or desire to participate in research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the fear, distrust ( George et al., 2014 ), and historical misconduct associated with the Tuskegee study ( Shavers et al., 2000 ) may be related to the low percentage of Black or African American participants (8.9%). On a more practical level, during the pandemic, women of color were more likely to be classified as essential workers ( Pope et al., 2021 ; Rogers et al., 2020 ) and faced unemployment if they did not continue to work ( Pew Research Center, 2020a ), which may have left women without the time or desire to participate in research.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) compared public health surveillance data of 162 pregnant women infected with COVID-19 to identify risk factors among Black ( n = 81, 50%) and non-Black ( n = 81, 50%) women. The results indicated that Black women infected with COVID-19 were significantly more likely to have preterm birth ( p = .026) and be exposed to COVID-19 at work ( p = .020) than non-Black women infected with COVID-19 ( Pope et al., 2021 ).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…people. [7][8][9] We compared the characteristics of pregnant people with and without laboratory-confirmed SARS-CoV-2 infection in Massachusetts.…”
mentioning
confidence: 99%
“…This comparison is critical to identify disparities and enrich our understanding of who is being most impacted by COVID-19 during pregnancy, especially as initial hospital-based and community-level studies suggest that racially and ethnically minoritized groups might experience higher rates of SARS-CoV-2 infection during pregnancy when compared with non-Hispanic White pregnant people. 7 - 9 We compared the characteristics of pregnant people with and without laboratory-confirmed SARS-CoV-2 infection in Massachusetts.…”
mentioning
confidence: 99%